Effect of Work Discipline on Employee Performance with Employee Job Satisfaction As A Mediation Variable - Susbiyantoro Susbiyantoro; Janaka Janaka; Mohammad Dadan Sundawan; Sandi Nasrudin Wibowo; Ade Solahudin (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The aim of this study for knowing influence discipline work by Partial nor simultaneous to performance employee with satisfaction work employee as variable mediation at PT. Trihamas Finance. Type study this use type associative and method study quantitative. research population take it to PT. Trihamas Finance amounted to 54 employees and a sample of 54 respondents. The sampling technique is non-probability sampling saturated. Method this data collection is method survey, data obtained processed use help device IBM SPSS 25.0 software for Windows, engineering data analysis multiple linear regression. Research results could concluded that variable discipline work with score tcount > ttable namely 11,921 > 1,675 and the value of significant 0.000 < 0.05 with thereby discipline work have influence significant to performance employee , variable satisfaction work employee with score tcount > ttable namely 13,592 > 1,675 and the value of significant 0.000 < 0.05 with thereby variable satisfaction work have influence significant , variable performance with score Fcount > Ftable namely 95.190 > 3.18 and the value of significant 0.000 < 0.05 with thereby variable discipline work and satisfaction work by simultaneous have influence positive and significant